Effects of Subcutaneous Ochratoxin-A Exposure on Immune System of Broiler Chicks - Khan, Shahzad Akbar (Toxins (Basel), 2019)
Ochratoxin A (OTA), an immunosuppressive mycotoxin, can increase the risk of many infectious diseases and contribute to economic losses to the poultry industry. The immunosuppressive effect has mainly been investigated through oral exposure; however, birds may also be contaminated through skin absorption. The present study investigated the influence of OTA exposure on the defense system of broiler chicks through the subcutaneous route and including low doses. Groups of broiler chicks (Cobb), 05 days old, were exposed to subcutaneous inoculation of OTA at concentrations of 0.1; 0.5; 0.9; 1.3; and 1.7 mg OTA/kg body weight. The size of the lymphoid organs, circulating immune cells, and total IgY and IgA levels were evaluated 21 days post inoculation. Subcutaneous OTA exposure decreased the weight of the thymus, spleen, and bursa of Fabricius, and leukocytopenia (p < 0.05) was detected in chicks of the OTA treated groups. In a dose-dependent way, decreased levels of circulating lymphocytes and heterophils (p < 0.05), and increased levels of monocytes (p < 0.05) were detected. Decreased IgY and IgA serum concentrations were noted in the OTA treated groups (p < 0.05). In conclusion, subcutaneous OTA exposure induces immunosuppression even at low levels.